IMPACT OF ENVIRONMENTAL FACTORS ON OUTBREAK OF DISEASES IN THE MUGA CROPS, ANTHERAEA ASSAMA, WESTWOOD (LEPIDOPTERA: SATURNIIDAE), IN KAMRUP DISTRICT (ASSAM) - RASHMIMALA KAKOTI (The Bioscan, 2011)
Population growth of the Muga crops , Antheraea assama Westwood (Lepidoptera:Saturniidae), an important bioresources of Assam, were analysed with respect to various agro-climatic conditions during the year Dec.2006- Dec.2009. Experimental data showed that the intensity of diseases became high at winter season (Dec.-Feb.). Two microbial diseases caused by protozoa and bacteria were seemed to be appear in devastating manner in winter crops, which were identified as ‘Pebrine’ and ‘Flacherie’ respectively. Less frequently, autumn (Sep.- Nov.) crops were also attacked by flacherie. Rate of larval mortality was found to be highest (92.66%) in winter crops infected with bacterial flacherie. Pebrine has claimed 61.3% of the larval life in winter crops. Death related to the impairment of larval moulting was identified in winter crops. However, mortality rate was minimum in spring (March-May) and summer (June-Aug.) seasons. No incidences of viral and fungal infections were recorded during the experimental periods.